2020
DOI: 10.1177/0194599820915487
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Kadish and Modified Dulguerov Staging Systems for Olfactory Neuroblastoma: An Individual Participant Data Meta‐analysis

Abstract: Objective To compare the Kadish and the modified Dulguerov staging of individual participants to determine the impact of stage and other prognostic factors on disease-free (DFS) and overall survival (OS). Data Sources Systematic review of EMBASE, MEDLINE, Cochrane Library, and CINAHL databases. Review Methods The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) was followed for this study. Articles including patients with olfactory neuroblastoma (ONB) staged with both Kadish and Dulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…In rare cases, induction CT may be indicated before definitive therapy 5 . Historically, open craniofacial approaches were utilized; however, over the past 2 decades there has been a shift towards endoscopic approaches with comparable oncologic outcomes demonstrated in appropriately selected patients 1,3,7 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In rare cases, induction CT may be indicated before definitive therapy 5 . Historically, open craniofacial approaches were utilized; however, over the past 2 decades there has been a shift towards endoscopic approaches with comparable oncologic outcomes demonstrated in appropriately selected patients 1,3,7 …”
Section: Introductionmentioning
confidence: 99%
“…1,3,7 Multiple staging systems have been proposed to provide prognostic information and guide treatment decisions; however, no system has been universally accepted, and the generalizability of staging systems derived from single institutional experiences has been questioned. 1,3 Surveillance Epidemiology and End Results (SEER) database studies have demonstrated that modified Kadish (mKadish) staging, lymph node involvement, and age at diagnosis are significant prognostic factors. Hyams grade, a pathologic grading system, has also been utilized to determine prognosis and outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, there is no uniform staging standard for ONB. The modi ed Kadish staging system proposed by Morita and his colleagues [6] has been shown to be related to prognosis and used to guide tumor management and treatment [7]. It is used in many studies to classify ONB [8].…”
Section: Introductionmentioning
confidence: 99%